PEMBUATAN DAN UJI ORGANOLEPTIK SEDIAAN SERBUK INSTAN DAUN KATUK ( Sauropus androgynus-(L) Merr ) DAN TEMULAWAK (Curcuma xanthorrhiza Roxb) - Muhammad, Gunawan; Djamaluddin, Agus; Farhan, Farhan (Sekolah Tinggi Ilmu Kesehatan Holistik, 2018)
Background: Breast milk (ASI) is a good source of protein for babies, but some mothers breastfeed late breast milk so it is not smooth. Empirically known katuk leaves and temulawak can increase milk production. So an instant powder preparation was made from katuk and temulawak leaves. Objective: Make and determine the formulation of the preparation of instant powder from katuk and temulawak leaves which is done by organoleptic test. Method: Action research in the form of a single treatment was arranged in a Completely Randomized Design (CRD) with 2 treatments and 5 replications. Single treatment is a dose of sugar consisting of 4 levels, namely G1 = addition of sugar 150 grams / liter, G2 = addition of sugar 200 grams / liter, G3 = addition of 250 grams / liter, and G4 = addition of sugar 300 grams / liter. Results: The addition of sugar in each sample affected the dosage form in different colors and the number of preparations produced in each sample was also different. Conclusion: Addition of sugar in each sample affects the dosage form in different colors of different flavors and the number of preparations produced by each sample is also different.